2000
DOI: 10.1590/s1415-47572000000300023
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a RAPD marker linked to the Co-6 anthracnose resistant gene in common bean cultivar AB 136

Abstract: The pathogenic variability of the fungus Colletotrichum lindemuthianum represents an obstacle for the creation of resistant common bean (Phaseolus vulgaris L.) varieties. Gene pyramiding is an alternative strategy for the development of varieties with durable resistance. RAPD markers have been proposed as a means to facilitate pyramiding of resistance genes without the need for multiple inoculations of the pathogens. The main aims of this work were to define the inheritance pattern of resistance present in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…Alleles: None reported. Markers: The OPAZ20 950 RAPD marker previously reported linked (7.1cM) to the Co-6 gene (Alzate-Marin et al, 2000), was also reported to be linked (2.2cM) to the co-8 in the cultivar AB 136 (Alzate-Marin et al, 2001b). The data also support the lack of independence of Co-6 and co-8.…”
Section: Locus Co-8mentioning
confidence: 98%
“…Alleles: None reported. Markers: The OPAZ20 950 RAPD marker previously reported linked (7.1cM) to the Co-6 gene (Alzate-Marin et al, 2000), was also reported to be linked (2.2cM) to the co-8 in the cultivar AB 136 (Alzate-Marin et al, 2001b). The data also support the lack of independence of Co-6 and co-8.…”
Section: Locus Co-8mentioning
confidence: 98%
“…2 ) and Perry Marrow (Co-1 3 ), but also in lines G 2333 (Co-4 2 , Co-5 and Co-7) and PI 207262 (Co-4 3 and Co-9) (Alzate- Marin et al 2003;Costa et al 2001). The band was also absent in the kidney bean cultivars Chardonnay and ROG 802 indicating they carried gene Co-1, which was supported by their race reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The RAPDs and SSRs markers are economically inexpensive and easy to use compared to RFLP and AFLPs. They have been employed to construct genetic linkage maps and for molecular tagging of various agronomic traits in melon (Oumouloud et al, 2008; Tezuka et al, 2009), pea (Janila and Sharma 2004; Vijayalakshmi et al, 2005), cabbage (Yu et al, 2009), pigeonpea (Dhanasekar et al, 2010; Kotresh et al, 2006), castor bean (Singh et al, 2003), pea (Tiwari et al, 1998), mungbean (Selvi et al, 2006), wheat (Gupta et al, 2006; Kumar et al, 2006), Phaseolus vulgaris (Caixeta et al, 2003; Martin and Menarim 2000), Glycine max (Zheng et al, 2003), Vicia faba (Avila et al, 2003), sorghum (Singh et al, 2006), common bean (Johnson et al, 1995; Young and Kelly 1997), groundnut (Mondal et al, 2007). …”
Section: Discussionmentioning
confidence: 99%